Chiral‐Zn(NTf2)2‐Complex‐Catalyzed Diastereo‐ and Enantioselective Direct Conjugate Addition of Arylacetonitriles to Alkylidene Malonates. Issue 48 (15th October 2013) - Yao, Jingjing; Liu, Xiaohua; He, Peng; Zhu, Yin; Lian, Xiangjin; Lin, Lili; Feng, Xiaoming
Abstract Chiral N, N′‐dioxide/Zn(NTf2)2 complexes were demonstrated to be highly effective in the direct asymmetric conjugate addition of arylacetonitriles to alkylidene malonates under mild conditions. A wide range of substrates were tolerated to afford their corresponding products in moderate‐to‐good yields with high diastereoselectivities (82:18–>99:1 d.r.) and enantioselectivities (81–99 % ee). The reactions performed well, owing to the high Lewis acidity of the metal triflimidate and a ligand‐acceleration effect. The N, N′‐dioxide also benefited the deprotonation process as a Brønsted base. The catalytic reaction could be performed on the gram‐scale with retention of yield, diastereoselectivity, and enantioselectivity. The products that contained functional groups were ready for further manipulation. In addition, a possible catalytic model was proposed to explain the origin of the asymmetric induction.